El certificado médico prenupcial en Antioquia (Colombia), 1933-1936 (2017)
ABSTRACT: Through the requirement of a medical certificate between 1933 and 1936, health authorities in the Colombian Antioquia department sought to regulate the physical and moral conditions of men and women who wanted to marry. The aim of this bureaucratic procedure was to prevent the birth of individuals who may become a burden to the State, and to promote the health and general welfare. Based on reports from physician and municipal health inspectors of the time, this article discusses the way in which this measure was unveiled to the population. It also highlights some of the challenges to enforce it due the disinterest of the Catholic Church, the low presence of physician in areas away from the municipalities, and the lack of infrastructure to carry out the required tests.